Factors Affecting the Practice of Birth Spacing among Women attending Post Natal Clinic in Zango Primary Health Care Bauchi - Maimuna, Muhammad; Musa, Muhammad Maryam; Salisu, Umar Muhammad; Dambam, Muhammad Fatima (THRIVE Health Science Journal, 2026)
In Nigeria, the fertility is currently 5.71% birth per woman and it’s one of the 7 largest in the world and the 3rd largest in Africa. The effective use of modern contraceptive methods by women of reproductive age in Nigeria is affected by many factors including prevalent negative attitudes and perceptions about some methods, inadequate knowledge about the various methods, unavailability, accessibility, complexity as well as strong cultural and religious oppositions to modern contraceptive methods. A cross-sectional descriptive design survey was carried out among women of reproductive age at Sabon Gari Primary Healthcare Center Dass. A total of 200 respondents were recruited for the study. A self-constructed questionnaire was used for data collection. Data were analyzed using SPSS version 20.0 and data were presented in frequency tables, percentages, graphs and pie charts. The results showed that 200 (100%) had used birth spacing and most 120 (60%) had used birth spacing for more than 4 months, 150 (75%) reported that non availability of birth spacing affected its utilization, 160 (80%) agreed that someone’s earning affected birth spacing practices among women, 150 (75%) agreed that unemployment hindered the practice of birth spacing, 120 (60%) were discouraged by their friends from using the birth spacing method they were using, 160 (80%) reported experiencing side effects of the methods they were using, 150(75%) were due to lack of formal education, 140 (70%) respondents reported that their husbands did not know about their current use of birth spacing, 180 (90%) reported that their culture did not promote the use of birth spacing among women, 170 (85%) reported that their religion did not support the use of birth spacing among women.